2013
DOI: 10.1177/0042098013478233
|View full text |Cite
|
Sign up to set email alerts
|

Vancouver’s “EcoDensity” Planning Initiative: A Struggle over Hegemony?

Abstract: The proclaimed aim of EcoDensity, an initiative of the former mayor of Vancouver, Canada, was the achievement of a more sustainable city development through densification of existing neighbourhoods. Since the invention of EcoDensity in summer 2006 it has become a highly debated topic. This paper aims at a critical analysis of how a planning strategy of densification tried to tie itself onto a discourse of sustainability, and also how it had to re-invent and reform itself through contestation and public debate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 12 publications
1
45
0
1
Order By: Relevance
“…Starting from the paper by While et al (2004), the concept sustainability fix has increased the understanding that local policy-making for urban sustainability is crucially translocal (e.g. Dierwechter, 2010;Jocoy, 2017;Lang & Rothenberg, 2017;Long, 2016;Pirro & Anguelovski, 2017;Rosol, 2013;Temenos & McCann, 2012;Tretter, 2013;Vogel, 2016). In these studies, sustainability fix is analysed as a general goal for urban sustainability, considering the entrepreneurial character of cities.…”
Section: Sustainability Fix As a Part Of Strategic Planning Narrativesmentioning
confidence: 99%
“…Starting from the paper by While et al (2004), the concept sustainability fix has increased the understanding that local policy-making for urban sustainability is crucially translocal (e.g. Dierwechter, 2010;Jocoy, 2017;Lang & Rothenberg, 2017;Long, 2016;Pirro & Anguelovski, 2017;Rosol, 2013;Temenos & McCann, 2012;Tretter, 2013;Vogel, 2016). In these studies, sustainability fix is analysed as a general goal for urban sustainability, considering the entrepreneurial character of cities.…”
Section: Sustainability Fix As a Part Of Strategic Planning Narrativesmentioning
confidence: 99%
“…This has been seen to promote situations in which the practices and power relations of politico-administrative processes are obscured (e.g. Beveridge, 2012;Lester & Reckhow, 2012;Rosol, 2013). On the other hand, some of these studies have demonstrated how network governance may multiply local democracy into coexisting local democracies applying and reflecting different democratic ideas, practices and participants (Häikiö, 2007(Häikiö, , 2010MacLeod, 2011;MacLeod & Jones, 2011;Sweeting & Copus, 2012).…”
Section: Government Meets Network Governance: Conflicting Concepts Rmentioning
confidence: 99%
“…Although the original formulation of the sustainability fix was developed in the United Kingdom, the concept has since seen application elsewhere, including Vancouver (Kear, 2007;Quastel, 2009;Quastel et al, 2012;Rosol, 2013) and other cities (e.g. Krueger & Gibbs, 2007;Long, in press;Temenos & McCann, 2012).…”
Section: Urban Agriculture and Neoliberalismmentioning
confidence: 99%